Clinical Consensus Statement: Vaginal Energy-Based Devices. Issue 10 (October 2022) - Alshiek, Jonia; Garcia, Bobby; Minassian, Vatche; Iglesia, Cheryl B.; Clark, Amanda; Sokol, Eric R.; Murphy, Miles; Malik, Shazia A.; Kimble, Alexis; Shobeiri, S. Abbas
Abstract : Abstract: This clinical consensus statement on vaginal energy-based devices (EBDs) reflects an update by content experts from the American Urogynecologic Society's EBD writing group. In 2019, the American Urogynecologic Society's EBD writing group used a modified Delphi process to assess statements that were evaluated for consensus after a structured literature search. A total of 40 statements were assessed and divided into 5 categories: (1) patient criteria, (2) health care provider criteria, (3) efficacy, (4) safety, and (5) treatment considerations. Of the 40 statements that were assessed, 28 reached consensus and the remaining 12 did not. Lack of evidence was among the main reasons that vulvovaginal EBD treatment statements did not reach consensus. In March 2022, these statements were reassessed using the interim literature.